Effect of American College of Surgeons Level 1 Trauma Center Designation on Management of Adult Severe TBI Patients. (1st September 2019) - Helton, Matthew; Porter, Austin; Thomas, Kevin; Henson, Jeffrey C; Sifford, Mason; Scott, Hayden; Rodriguez, Analiz; Sexton, Kevin
Abstract: INTRODUCTION: Severe traumatic brain injury (TBI) remains a leading cause of morbidity and mortality. There is a wide variability in treatment paradigm for patients with severe TBI. American College of Surgeons (ACS) level 1 trauma centers have access to 24 h neurosurgical coverage. In this study, we use the National Trauma Database (NTDB) to evaluate if ACS trauma center designation correlates with the management and outcomes of severe TBI in adults. METHODS: Adult patients (<65 yr) with a severe isolated nonpenetrating TBI were identified in the NTDB from years 2007 to 2014. ICD-9 procedure codes were used to identify primary treatment approaches: intracranial pressure monitoring and cranial surgery. Multivariate logistic regression was used to determine the impact of ACS designation on procedures and patient outcomes. Patient and injury characteristics were included in the analysis. RESULTS: A total of 54 769 TBI patients were identified. Among those, 22 316 (42%) were treated at an ACS level 1 trauma center and 31 835 (58%) were treated elsewhere. Level 1 designated patients had significantly more intracranial pressure (ICP) monitors placed (12.3% vs10.8%; P  < .0001) and more cranial surgeries performed (17.7% vs 15.7%; P  < .0001). A greater percentage of patients were admitted to the intensive care unit (ICU; 89.9% vs 83.9%; P  < .0001) and had a longer hospital stay (16.1 vs 15.2; P  < .0001) at ACS level 1 trauma centers. In a regression analysis, patients at level 1 centers were associated with a 14% and 17% increased odds of obtaining a cranial surgery or ICP monitor, respectively. Patients treated at a level 1 center were associated with a 6% decrease in odds of mortality ( P  = .01). CONCLUSION: ACS level 1 designation did correlate with increased rates of neurosurgical intervention and ICU admissions. This translated into patient outcomes as those treated at level 1 facilities were associated with lower rates of mortality.